9 Change in patient-reported outcomes following meniscal repair compared with resection in young adults: secondary analyses from a prospective cohort study. (April 2019) - Pihl, Kenneth; Englund, Martin; Christensen, Robin; Lohmander, Stefan; Jørgensen, Uffe; Nissen, Nis; Fristed, Jakob V; Thorlund, Jonas B
Abstract : Introduction: In young adults, meniscal repair may be an alternative to resection. We compared change in patient-reported outcomes from before to 52 weeks after arthroscopic surgery in younger patients having either meniscal repair or resection. Materials and methods: Patients aged 40 or younger from the Knee Arthroscopy Cohort Southern Denmark (KACS) study undergoing arthroscopic meniscal surgery. Patients completed the Knee injury and Osteoarthritis Outcome Score (KOOS) online at pre-surgery, 12 and 52 weeks follow-up. Between-group differences in change in a composite of 4 of 5 KOOS subscales (KOOS4 ) from baseline to 52 weeks were analyzed using repeated measures mixed linear models. Results: 118 patients having meniscal resection (mean age 32 [SD 7], 66% men, mean baseline KOOS4 score 48.3 [SD 17]), and 24 patients having meniscal repair (mean age 26 (SD 6), 67% men, baseline KOOS4 score 47.1 [SD 16]) were included. At 52 weeks both groups had improved, but patients having repair experienced less improvement in KOOS4 scores than patients having resection (adjusted mean difference in change −13.0, 95% CI: −21.1; −4.9, p=0.002). Sensitivity analysis excluding patients having additional surgery in the index knee within the 52 weeks follow-up (repair: 32%; resection 9%) yielded similar results. Additional subgroup analysis including only patients with non-degenerative longitudinal-vertical tears, displayed even less improvement in the repair group compared with the resection group (adjusted mean difference in change −22.9, 95% CI: −32.5; −13.2, p<0.001). Conclusion: In this prospective cohort, patients having meniscal repair experienced less improvement after 1 year than patients having meniscal resection.